Evaluation of biosafety standards in health professionals at a public hospital and a rehabilitation center in Aracaju city (Research, Society and Development, 2022)
Biosafety approaches prevention as a primordial topic for workers, especially health professionals, due to the work environment that presents most susceptibility to accidents. It is about avoiding health risks through the use of personal protection equipment and collective protection equipment, in addition to following the rules that minimize contamination. However, it is necessary to emphasize the importance of prior knowledge about biosafety during the academic phase to remain with the knowledge through the professional phase. Thus, the research aimed to evaluate the applicability of biosafety rules in hospital and outpatient place. This is an observational, cross-sectional, field study, with quali-quantitative nature, carried out after Informed and Free Consent Form signed by the health professionals and academic. Data collection was carried out at Ninota Garcia Health Center and at Governador João Alves Filho Health Emergency Hospital. The sample was by convenience, consisting of 114 participants. Regarding the results achieved, it was possible to show that health academics showed greater adherence to biosafety rules, while professionals need interventions to update their knowledge about safety measures. Thus, they were highlighted as beneficial disadvantages of frequent updating of preventive rules that reflect the use of personal protection equipment, as well as the reduction of the acidentes risk, with training in biosafety rules being an essential condition for students and health professionals.